Board characteristics and integrated reporting in an emerging market: evidence from India - Manimore Makri; Leo Themjung Makan; Kailash Chandra Kabra (AJAR (Asian Journal of Accounting Research), 2024)
Purpose – This paper aims to examine the influence of board characteristics on the integrated reporting quality (IRQ) of Indian-listed companies. Design/methodology/approach – The study uses a sample of 197 firms from the BSE 500 for the years 2017–2018 to 2019–2020. The proposed hypotheses are tested using two-stage least squares regression. Findings – The study documents a positive influence of board size, board independence and gender diversity on IRQ. The study also finds that board activity and role duality are insignificant with IRQ. Among the firm-specific characteristics, variables such as firm size, profitability and capital intensity positively influence IRQ. Originality/value – The current study presents the first investigation in the context of India on the various board characteristics influencing IRQ. The study reiterates the role that gender-diverse boards have in improving information transparency. Policymakers can therefore drive adoption by recommending changes in board characteristics and increasing the quota for women on boards.